Removal of cobalt and nickel from zinc sulphate solutions using activated cementation - Boyanov B.; Konareva V.; Kolev N. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The influence of different parameters (duration, temperature, zinc dust quantity, concentration of activators - copper and antimony) on the process of activated cementation of Co and Ni has been studied. We have worked with industrial zinc sulphate solutions. During the process of activated cementation of Co and Ni, copper (involved as CuSO4.5H2O) and antimony (involved as Sb2O3) were used as activators. The lowest values of Co content have been obtained at a temperature of 80-85 oC, CCu = 200-300 mg/dm3 and 18 multiple surplus of zinc dust. After adding Cu to the solution, mainly the cementation of Ni is activated, and that of Co is activated to a lower degree. It was found that when GSb : GCo ratio is between 0.5 : 1 and 2 : 1, the solution is purified from Co and Ni to a great degree. After intensive stirring and increasing the duration of the process the cement sediments dissolve reversely. This holds true of Co to a greater extent, as compared to Ni. The results obtained will be used to establish optimal conditions for the carrying out of activated cementation in Zinc Production Plant in KCM SA, Plovdiv.